Türk resim sanatında Galatasaray sergileri - Taşdelen, Ömer (My University, 2003)
Türk Resim Sanatı'nda önemli bir yeri olan Galatasaray Sergileri, 1916'da Osmanlı Ressamlar Cemiyeti tarafından başlatılmış ve 1951'e kadar her yıl düzenli olarak yinelenmiştir. Savaş yıllarında da sürdürülen sergilere her yıl küçük bir katalog da eşlik etmiştir. Galatasaray Lisesi'nin tatile girdiği yaz mevsiminde, özellikle de temmuz-ağustos aylarında bir ay süreyle açılan Galatasaray Sergileri, eğilim ayrımı yapmamakla birlikte Osman Hamdi kuşağı karşısında anlatım dili olarak daha çok izlenimci estetiği benimseyen sanatçıların bir araya geldiği bir etkinlik olarak tanınmıştır. 1914 ya da Çallı Kuşağı adlarıyla anılan ve I. Dünya Savaşı'nın başlamasıyla birlikte Fransa'dan yurda dönen bir grup sanatçı tarafından 1916'dan itibaren düzenlenmiş ve uzun yıllar Türk resim sanatı içinde etkin bir rol üstlenmiş ve bir anlamda Paris'teki Salon'a benzer bir kimlik kazanmıştır. Osmanlı döneminde bir sanatçı derneğinin etkinliği olarak başlatılan, saray çevresi tarafından destek gören bu sergiler Cumhuriyet'in ilanından sonra da sürdürülür. Ülkemizdeki en önemli plastik sanatlar etkinliklerinden biri olarak görülen Galatasaray Sergileri, kent halkı, aydınlar ve sanat çevrelerince her yıl beklenen bir kültür olayı olmuştur. 1950'li yıllara değin kendini gösterme, sanatçı olarak kabul görmek, büyük ölçüde Galasataray Sergileri'nde eser sergilemekle sağlanmıştır. Sonuç olarak, 36 sergide 340 sanatçı 5.817 yapıt sergilemiştir ki, dönemin sanatsal üretimine dair çok önemli bir veri oluşturmaktadır. 340 sanatçının yarıdan fazlası, bu çalışmayla ilk kez literatüre girmiştir.

The Galatasaray Exhibitions, which are of a certain importance for the history of Turkish art, were initiated by the Ottoman Artists Association in 1916. They had been repeated every year until the year 1951, continueing even during the war years; and had each year been accompanied by the publication of a catalogue. Though the Galatasaray Exihibions -which were open for a month in summer time, when the Galatasaray College was on holiday, especially in july or august- had never had any special sympathy towards any artistic inclination, they were often defined as activities in which artists who, as opposed to the Osman Hamdi Generation, prefered rather an impressionist aesthetics as their narrative language came together. Since 1916 they had been organized by a group of artists who are often referred to as 1914 or Çallı Generation and who returned from France to Turkey with the beginning of the first world war, and they had had a quite active role for the Turkish art for long years, in some sense they had gained an identity which had been quite similar to that of the Hall in Paris. Initiated under the Ottoman rule as the activity of an artists' association with the support of the Ottoman palace, the exhibitions had been continued even after the foundation of the Turkish republic. Being regarded as one of the the most important activities in the field of the Turkish plastic arts, these exhibitions had been a real cultural phenomenon for the public, just as the intellectuals and artists' circles. Until 1950's, for the artist, to a great extend, to show up in the public scene, to prove his talent was to exhibit works in the Galatasaray Exhibitions. In conclusion, in 36 exhibitions, 340 artists had exhibited 5817 works, which is a very important datum about the artistic productiveness of the period. More than a half of these artists were introduced to the public scene by these activities.
Keywords: Resim Sanatı; Resim, Türk